Røys som fenomen. Rydning eller grav? (AmS-Varia, 2020)
Cairns in one form or another are the most common type of prehistoric structure encountered during archaeological surveys in Rogaland County, southwestern Norway. In Norway, the responsibility for pre-development archaeological investigations is divided between county archaeologists and regional museums with the former undertaking site identification surveys and the latter carrying out subsequent excavations. Archaeological surveying is typically non-invasive and distinguishing burial cairns from clearance cairns often proves to be a difficult task. It is frequently argued that separating the two categories based on size and form alone is not sufficient. In this article, it is shown that, in addition to visual analysis, an understanding of the surrounding prehistoric landscape within which the cairn is situated is crucial when interpreting these structures. The interpretive utility of new methodologies such as Lidar and analysis of soil identification maps are also highlighted. Arguments are based primarily on data from localities containing cairns encountered during the E39 Ålgård–Hove project carried out in 2016 by Rogaland County, as well as a site excavated by the Museum of Archaeology, University of Stavanger in 2011.